ISU-ISU PEGUAM SYARIE DI MALAYSIA - Abu Bakar, Md Zawawi (Jurnal Syariah, 2019)
Syarie lawyers have the responsibility to represent their clients in the Syariah Court. The lawyers are only allowed to practice law within the state that appointed them as prescribed under the states ’ statute. Such situation has created inconsistency, which is the main issue plaguing the current Syariah institution. The inconsistency exists when the administration of the Syarie lawyers is under the different enactment and Kaedah Peguam Syarie from one state to another. The inconsistency includes the administering of qualification, appointment procedure and requirement, disciplinary action and so forth . These caused by the jurisdiction of states statute. Moreover, the issue relating to Jawatankuasa Peguam Syarie will be discussed. This committee does not possess the authority concerning the formation of law firm, insurance scheme, and the control over the firm ’s annual financial account. Finally, there is the need to legislate the main act in order to standardize the administering of Syarie lawyers throughout Malaysia.